Putting evolution in elimination: Winning our ongoing battle with evolving malaria mosquitoes and parasites - Huijben, Silvie (Evol Appl, 2017)
Since 2000, the world has made significant progress in reducing malaria morbidity and mortality, and several countries in Africa, South America and South‐East Asia are working hard to eliminate the disease. These elimination efforts continue to rely heavily on antimalarial drugs and insecticide‐based interventions, which remain the cornerstones of malaria treatment and prevention. However, resistance has emerged against nearly every antimalarial drug and insecticide that is available. In this review we discuss the evolutionary consequences of the way we currently implement antimalarial interventions, which is leading to resistance and may ultimately lead to control failure, but also how evolutionary principles can be applied to extend the lifespan of current and novel interventions. A greater understanding of the general evolutionary principles that are at the core of emerging resistance is urgently needed if we are to develop improved resistance management strategies with the ultimate goal to achieve a malaria‐free world.